KONFLIK PEKERJAAN-KELUARGA : TIPE KONFLIK DAN DAMPAKNYA PADA KEPUASAN - Jovi Sulistiawan; Aris Armuninggar (MIX: JURNAL ILMIAH MANAJEMEN, 2017)
Abstract. This study examines the effect of work-family conflict on satisfactionoutcomes that consist job satisfaction, marital satisfaction and life satisfaction. Thisstudy distinguished work-family conflict into three types, job-spouse, job-parent andjob-homemaker conflict. Using 102 doctors from RSUD Dr Soetomo Surabaya, wefound that only job-homemaker conflict has insignificant effect on three satisfactionoutcomes. The main reason underlying this result is the tendency of modern family thatuse servant to help them doing household duties. Both job satisfaction and maritalsatisfaction are strong predictor to life satisfaction.Keywords : work-family conflict, satisfaction outcomes